2006
DOI: 10.1021/jp060113q
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fundamental Transport Properties and Thermodynamics in Diglyme−Salt Solutions

Abstract: Ionic mobility, the thermodynamics of ionic association, and the structure of associated species are studied in solutions of diglyme containing either lithium triflate or tetrabutylammonium triflate. Infrared spectroscopic, PFG NMR, thermodynamic, and crystallographic data suggest that the solute species existing in diglyme-lithium triflate are "free" ions, contact ion pairs, and dimers. Equilibrium constants, S(o), deltaH(o), and deltaG(o) are calculated for processes occurring between these species. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 22 publications
6
62
0
Order By: Relevance
“…This is directly reflected by the c salt -dependence of the K's (Table 1) as well as by the fact the estimated K values from Bjerrum theory are very different. A further confirmation comes from the results in the case of diglyme [33]. Very similar concentrations for c + , c − , c pair are found there, yet extremely different γ values are derived as a consequence of the very different dielectric constants.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This is directly reflected by the c salt -dependence of the K's (Table 1) as well as by the fact the estimated K values from Bjerrum theory are very different. A further confirmation comes from the results in the case of diglyme [33]. Very similar concentrations for c + , c − , c pair are found there, yet extremely different γ values are derived as a consequence of the very different dielectric constants.…”
Section: Resultssupporting
confidence: 69%
“…1e [32,33]. As we found a linearity between total area comprising of these three peaks and c salt , we followed the procedure given in [33] in order to derive concentrations of specific species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the interactions between Ni(mnt) 2 − and ( n -Bu) 4 N + are expected to be relatively weak because of the steric hindrance of the positively charged nitrogen atom by the bulky n -butyl groups. This is supported by infrared studies of ( n -Bu) 4 NCF 3 SO 3 in diglyme 39 and triglyme, 40 which showed that only free ( n -Bu) 4 N + and CF 3 SO 3 − were present. This was not the case for LiCF 3 SO 3 in diglyme 39 and triglyme 40 as well as NaCF 3 SO 3 in tetraglyme; 41 mixtures of free ions, ion pairs, triple ions, and aggregates were found.…”
Section: Resultsmentioning
confidence: 57%
“…Solutions of LiCF 3 SO 3 in the same two solvents, however, contained free ions, contact ion pairs, and aggregates. 35,36 …”
Section: Discussionmentioning
confidence: 99%